Perdebatan dan Fenomena Global Legalisasi Pernikahan Sesama Jenis: Studi Kasus Amerika Serikat, Singapura, dan Indonesia - Anna Triningsih; Oly Viana Agustine (Jurnal Konstitusi, 2021)
Same sex marriage is currently an international and controversial issue. The issues drive people from around the world, with different culture, religion, and countries into a dividing debate: is same-sex marriage needs to be legalized or banned? The debates brought some countries in different stances, some legalize, some ban and criminalize, and some without clear or specific rules in banning or legalizing it. Due to the differences found between countries, this research aims to provide answer and conclusion to this crucial question: is same-sex marriage is a universal human rights, in which countries should recognize and legalize it? The results of this study show that same-sex marriage is not a phenomenon or a right that can be accepted and recognized in all countries, cultural settings, and religions. Therefore same-sex marriage does not fulfill the requirements to be said as a universal human right which absolutely must be recognized, accepted, and fulfilled by all countries (without exceptional) in the world. Therefore, the policy to legalize or prohibit same-sex marriage is entirely an open legal policy which can be freely chosen by each sovereign state. There is no obligation under international law to legalize or prohibit that matter because it is not a universal human rights and moral standard which can be enforced recognition and fulfillment in every country.